Shetty Test Challenges Ottawa Ankle Rules in Detecting Foot and Ankle Fractures: A Prospective Comparative Study - Konstantinos Makiev; Ioannis Vasios; Anthimos Keskinis; Reichan Molla Moustafa; Georgios Petkidis; Konstantinos Tilkeridis; Athanasios Ververidis; Efthymios Iliopoulos (Bulletin of Emergency and Trauma)
Objectives: Ankle joint injuries are among the most common orthopedic injuries and are associated with significant healthcare costs. To reduce unnecessary radiographic screening, diagnostic tools such as the widely accepted Ottawa Ankle Rules (OARs) have been developed. However, the accuracy of OARs in excluding fractures remains uncertain. Recently, a new diagnostic test, the Shetty Test (ST), has been introduced. This prospective comparative study aimed to evaluate the diagnostic accuracy of the “ST” in comparison to the “OARs” for detecting ankle and foot fractures.Methods: A total of 112 consecutive adult patients (>18 years old) were included in the study. They were presented to the Emergency Department of a University Hospital in Alexandroupolis due to an ankle or foot injury. Data were collected over 6 months, from November 2022 to May 2023.Results: The sensitivity of the ST was 68.4%, specificity was 76.3%, positive predictive value (PPV) was 37.1%, and negative predictive value (NPV) was 92.2%. For the OARs, sensitivity was 94.7%, specificity was 15%, PPV was 18.5%, and NPV was 93.3%. When at least one of the tests was positive, the sensitivity and NPV increased to 100%.Conclusion: The ST was found to be reliable; however, it did not outperform the OARs in this study. Nevertheless, when used in conjunction, the two tests significantly improved sensitivity and the NPV. Due to its simplicity and reproducibility, the ST could be a valuable tool in daily clinical practice, particularly for non-orthopedic emergency department personnel.